Evaluasi Aplikasi Pembayaran di Madrasah Tsanawiyah (MTs) Berbasis Website - Akhmad Fadjeri; Taufik Hidayat; Endang Wahyuningsih; Mokhamad Isro; Anisa Dwi Nurchayati (Jurnal Kridatama Sains dan Teknologi, 2026)
This research was conducted at MTs Ma'arif NU 01 Susukan from November to December 2024 with the aim of evaluating the development of a website-based Syahriyah Madrasah Application. The type of research used was Research and Development (R&D) with the ADDIE development model. The focus of paper publication was on the evaluation stage. Research data was obtained through interviews with competent media experts in their fields, then analyzed using a Likert scale (Aurora & Effendi, 2019). The validity test of the development results refers to the criteria set by Hidayat et al. (2024) a percentage of 75.01%–100% is categorized as very valid, 50.01%–75% is quite valid, 25.01%–50% is invalid, and 0%–25% is very invalid. The results of the research evaluation showed that the developed application obtained an average SUS score of 63.25, which is in the fairly valid category. These findings indicate that the application is suitable for use in supporting the management of Syahriyah payments in madrasas, although further development is needed to improve quality, convenience, and user satisfaction. Evaluation of the results of the website-based Syahriyah Madrasah application can be an effective solution for increasing transparency and accuracy in school financial management.